Gaza : entre occupations et résistances de 1967 à 2009 - Ba, Daha Chérif (Études sur la Région Méditerranéenne, 2012)
In the aftermath of the over-equipped Israeli armed forces' victory in 1967, a large number of places and strategic sites of crucial importance have simply been wrested and progressively invested and then durably occupied by small contingents of euphoric Israelis strongly galvanized by the military successes achieved by their generals. Regarded as colonies by some, and also by those who advocate the Palestinian cause, yet taken as legitimate settlements for Jewish occupants, those much coveted lands are 136 in the West Bank and 19 in the narrow Gaza Strip for a total population of 208,000 Israelis living among 4 million Palestinians. Those occupations have however aroused much reticence on behalf of successive Israeli governments. It is quite meaningful that in the 1993 Oslo agreements on the recognition by Israel of the Palestinian authority, it has been able to obtain the maintenance of Israeli colonies in Palestinian territory. For that purpose, some roads have been exclusively built within Palestinian territory so as to connect those colonies to the Israeli territory. In any way, that situation is unbearable both for Palestinians living under occupation and Israeli colonists altogether? In short then, the germs of Palestinian people's resistance have been there since the foundation of the Hebrew state, and the resistance has inevitably been organized against Zionist forces settled in Arab land. To understand the grounds of the Palestinian people's resistance, it matters to dig into the genesis of the very complex relationship between Palestine and Israel. First and foremost, we make a short historical survey of the most outstanding facts in what has been called "the Palestinian question " including the First Intifada, and the Second Intifada. Then, we present the historical dimensions of the Gaza Strip, starting from the 13'h century A.D. until the Israeli occupation which starts in 1967, including the Egyptian preeminence in its geographical, demographic, urban and economic aspects. Thirdly, we analyze the repressive policies carried out by Israeli forces on the populations of Gaza; then the irresistible irruption of the Hamas forces into Gaza in the political spectrum and on the field of resistance against the Israeli annexing forces. We examine the course of those forces of resistance from the armed struggle to its acquisition ofpolitical and administrative power, as backed by a policy of pragmatic negotiations. Lastly, we try to see how the advent of US President Barack Obama could open new perspectives for lasting peace in Palestine and the broader region of the Middle-East.